COVID-19 PANDEMIC AS THE REASON FOR FORCE MAJEURE IN MOTOR VEHICLES CONSUMER FINANCING AGREEMENTS (STUDY AT PT SUMMIT OTO FINANCE BENGKULU BRANCH) - Hafidza Zia; Candra Irawan; Tito Sofyan (Universitas Bengkulu, 2022)
As an emergency, the COVID-19 pandemic is also known as a force majeure in civil law, therefore it could be one of the reasons for the postponement until the cancellation of the current agreement. Therefore, the Financial Services Authority as the institution authorized to regulate financial service activities stipulates OJK Regulation Number 14/POJK.05/2020 concerning Countercyclical Policy on the spreading impact of the 2019 Coronavirus Disease for Non-Bank Financial Services Institutions to optimize leasing business activities through financing restructuring. This thesis was completed through empirical research. This study aimed to describe and analyze the implementation of credit restructuring by PT. Summit OTO Bengkulu Branch to resolve late installment payments due to Force Majeure due to the impact of COVID-19, as well as to comprehend and know legal settlements related to delays in the implementation of motor vehicle installment payments at PT. Summit OTO of Bengkulu Branch due to COVID-19.The results of the research and discussion explain that the legal consequence of the spread of COVID-19 as a Force Majeure relative to the financing agreement is that the debtor must still fulfill his obligations/achievements to the debtor after COVID-19 ends. In its implementation, debtors are given credit relief through restructuring in accordance with the form of restructuring issued by leasing in the form of lowering interest rates, extending time, reducing principal arrears, reducing interest arrears, and other forms according to the verification and analysis of the Leasing party on debtors affected by COVID-19. Implementation of financing restructuring in PT. Summit OTO Bengkulu Branch until July 2021 has been realized as much as431 (four hundred and thirty-one) contracts financing. Restructuring of financing is carried out by extending the term of the agreement, delaying part of the payment of motor vehicle installments, and reducing the principal arrears during the period of restructuring of the financing.